Clinical and microbiological evaluation of the culture results of the patients with chronic dacryocystitis at a tertiary care hospital - Gümüşsoy, Murat; Çukurova, İbrahim and Ece, Gülfem and Atalay Çetinkaya, Erdem (ENT Updates, 2016)
Objective: In this study, we aimed to evaluate the isolated strains from the patients with chronic dacryocystitis and the relationship between different anatomical areas and their antibiotic susceptibilities. Methods: Fifty patients diagnosed with chronic dacryocystitis were included. Fifty patients underwent endoscopic endonasal dacryocystorhinostomy from March 2013 to April 2014. Swab samples were obtained from conjunctiva and inferior nasal meatus before surgery, obtained from lacrimal sac during surgery. Identification and antibiotic susceptibility of the isolated strains were performed by automated Vitek version 2.0 systems (BioMeriuex Inc., Marcy-l’Étoile, France). Results: A total of 39 (78%) female and 11 (22%) male patients were operated and 150 swab samples were evaluated. Bacterial growth was detected in 136 (90.6%) culture samples. A single (n=125; 91.9%) or two different (n=11; 9.1%) microorganisms were grown on culture media. The distribution of gram-positive strains (n=91) and gram-negative strains (n=56) were 61.90% and (38.10%), respectively. The most frequently isolated gram-positive isolate was Staphylococcus. Gram-negative isolates were susceptible to third-generation cephalosporins, cefepime and carbapenems while gram-positive isolates were susceptible to vancomycin, teicoplanin and linezolide. Conclusion: For methicillin-sensitive coagulase-negative Staphylococci and methicillin-resistance coagulase-negative Staphylococci, bacterial growth demonstrated similarities among three different compartments (conjunctiva, lacrimal sac and inferior meatus). In other words, growth of these microorganisms in one location points to their proliferation in the other location or vice versa. This data can be used to guide antimicrobial therapy for these cases; but further studies are required.